Contribuições à análise de qualidade do jornalismo na comunicação pública digital - Rothberg, Danilo [UNESP]; Vanzini, Kátia Viviane da Silva [UNESP] (My University, 2013)
Scientific research has shown remarkable advances in the formulation of criteria for assessing the quality of journalism practiced in the commercial media and public broadcasting, comprising aspects such as management models, business principles, parameters to the assessment of results and exercise of social responsibility. However, there are fewer investigations on the practice of journalism in digital public communication formats explored by government web portals. The contribution of this paper lies in a proposal of elements for the construction of parameters for evaluating the quality of journalism in the digital public communication. The proposal is inspired by criteria for evaluating the quality of commercial media and public broadcasting and suggests means for its application in the journalism practiced in the context of government web portals.

A pesquisa científica tem apresentado notáveis avanços na delimitação de critérios de avaliação de qualidade do jornalismo praticado em mídias comerciais e na radiodifusão pública, abrangendo aspectos como modelos de gestão, princípios de atuação, parâmetros de verificação de resultados e exercício de responsabilidade social. Mas permanece pouco investigada a prática do jornalismo nos formatos de comunicação pública digital explorados pelos portais eletrônicos de governo. A contribuição deste artigo reside na formulação de elementos para a construção de uma proposta de parâmetros de avaliação de qualidade do jornalismo na comunicação pública digital. A proposta é inspirada em critérios de avaliação de qualidade das mídias comerciais e de radiodifusão pública e sugere meios para sua aplicação no jornalismo praticado no âmbito dos portais eletrônicos de governo.
Contributions to the analysis of quality of journalism in the digital public communication
Keywords: Quality journalism; Public communication; Digital democracy; Government web portals; Qualidade no jornalismo; Comunicação pública; Democracia digital; Portais eletrônicos de governo